Exploring the Experiences of Dutch Parents Caring for Children with Profound Intellectual and Multiple Disabilities: A Thematic Analysis of Their Blogs - Liesbeth Geuze; Anne Goossensen (SAGE Publishing, 2021)
The current study analyzed blogs written by four Dutch parents of children with profound intellectual and multiple disabilities, with the aim of deepening the understanding of the parents' concerns. Thematic analysis was conducted and five main themes were identified: Dealing with uncertainties addressed the impact of unpredictability present in the everyday lives of parents, Love and loss described the complexity of concurrently cherishing the child and grieving various types of loss, Struggling with time, energy and finances detailed imbalances and struggles related to parents' personal resources, Feeling included in communities and society specified social consequences, and Relating to professional care services reflected on stress and support associated with professional care delivery. The study findings demonstrate how care professionals should acknowledge parents' vulnerabilities by being aware of their existential distress and empowering parents to exercise control of family thriving.